PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN PELANGGAN UNTUK MENINGKATKAN NIAT PEMBELIAN ULANG (Studi Pada Oli Sepada Motor Merek Eni di Kota Denpasar) - Tejantara, Andy; Sukawati, Tjok Gde Raka (E-Jurnal Manajemen; Vol 7 No 10 (2018)DO - 10.24843/EJMUNUD.2018.v07.i10.p17, 2018)
This study aims to determine the effect of marketing mix to customer satisfaction to improve repurchase intention. The study was conducted in Denpasar City with the number of samples taken as many as 120 people. The method used is non probability sampling. Data were collected by survey method which distributed questioner to respondent. Data analysis technique used is PLS (Partial Least Square). Based on the analysis results found that (marketing mix) product quality, price perception, distribution channel and promotion appeal positively and significantly influence to customer satisfaction. This shows that the better the quality of the product, the perception of the price, the distribution channels and the attractiveness of the promotion will create customer satisfaction. Customers who are satisfied with a product will create repurchase intentions. Companies can create repurchase intentions for their products through increased customer satisfaction.   Keywords: marketing mix, customer satisfaction, repurchase intention